Preparation and Characterization of Microencapsulated n-octadecane as Phase Change Materials (Journal of Fiber Bioengineering and Informatics, 2012)
In this paper, a kind of microcapsule containing phase change material of n-octadecane was successfullysynthesized based on in situ polymerization where trimethylol melamine and hexamethylol melaminewere shell materials. We used different emulsification time, reaction time and different treatment toimprove the quality of the microcapsules. The microcapsule and coated fabric were characterized bythe optical microscope, Scanning Electronic Microscope (SEM), laser diameter distribution machine andDifferential Scanning Calorimeter (DSC). The optical microscope and SEM pictures showed that thismicrocapsule has good surface configuration. Particle size with laser diameter distribution machinedisplayed that grains of the microcapsule were distributed evenly. The DSC results revealed the phase-changing temperature and enthalpy of the microcapsule.